Exploring EFL Students' Perceptions: The Role of AI Chatbots in Enhancing English Writing Skills - Masita; Hanif Maulaniam Sholah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This explanatory sequential mixed-methods study investigates how secondary EFL learners perceive and ethically integrate generative AI chatbots into academic writing. Grounded in an expanded Technology Acceptance Model (TAM), it addresses qualitative experiences and spiritual ethical boundaries within Islamic educational environments. Quantitative survey data were gathered from 20 MAN 1 Malang students, followed by semi-structured interviews with five selected participants, analyzed using Braun and Clarke’s thematic framework. Findings reveal high AI adoption; 100% of survey respondents agreed on task efficiency and grammar correction. Qualitatively, students utilize AI as an interactive scaffold to overcome writer’s block, structure outlines, and reduce writing anxiety. However, learners maintain critical agency regarding AI "hallucinations," expressing concerns over intellectual dependency, voice loss, and plagiarism. Rather than passive consumers, students display self-regulated agency through rigorous post-generation editing, such as lexical adaptation and structural re-engineering, to safeguard authorship. Crucially, this ethical boundary is deeply anchored in madrasah values emphasizing academic honesty and seeking spiritual blessings (barakah). Theoretically, this study broadens TAM into faith-based digital contexts, practically suggesting educators foster prompt engineering and critical editing over outright technology bans.